Modified graphite coated soft particles, preparation method thereof, profile control water shutoff agent and application of profile control water shutoff agent
By covering the surface of the rubber particles with modified graphite, the problem of rubber particles being easily oxidized and sticking too quickly in high-temperature and high-salt environments is solved, and efficient sealing effect and long-term stability are achieved in deep oil reservoirs.
Patent Information
- Application Number
- CN202411006954.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-25
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-07-25
AI Technical Summary
The rubber particles in existing high-temperature and high-salt reservoirs are prone to oxidation failure in high-temperature and high-salt environments, and float at low density and stick too fast, resulting in difficulty in deep injection and poor sealing ability.
Using modified graphite coated soft particles, the first modified graphite and second modified graphite are covered on the surface of the rubber particles to enhance the oxidation resistance and cohesion ability, and the density of the particles is close to the formation water through density regulators, delaying the viscosity. Gather and increase the sealing strength.
Maintain long-term stability in high-temperature and high-salt environments, extend the effective period by ≥90 days, improve the viscosity and sealing strength, and ensure deep injection and effective sealing.
Smart Images

Figure CN119161862A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oilfield chemical profile control and water plugging, and in particular to a modified graphite coated soft particle and a preparation method thereof, a profile control and water plugging agent and an application thereof. Background Art
[0002] With the development of unconventional oil and gas resources in my country, the exploitation technology of deep oil reservoirs has become more and more perfect, and has become a research hotspot and strategic focus in the international energy field. These oil reservoirs are widely distributed all over the world, including but not limited to deep-sea sedimentary basins and deep structures in desert areas. Together, they constitute a huge untapped energy reserve on the earth. However, the extreme environment of high temperature, high pressure and high salinity has posed unprecedented challenges to existing exploration and development technologies. The average burial depth of deep oil reservoirs exceeds 4,500 meters, and they have the characteristics of ultra-high pressure (>120MPa), ultra-high temperature (≥130℃), and ultra-high salt (≥20Wmg / L). Deep oil reservoirs are usually located in areas with complex geological structures and may contain traces of multiple tectonic movements, such as faults and folds. These complex geological structures affect the connectivity of the reservoirs and the fluidity of the fluid. Deep oil reservoirs are mainly developed by water drive. The uneven distribution of formation porosity and permeability may lead to complex oil and water distribution, increase the uncertainty and difficulty of exploitation, and easily lead to water channeling. Injecting plugging agents into water channeling channels to form plugging has become an effective way to help further develop deep oil reservoirs, and the core is the research and development of plugging agents. Rubber particles have advantages such as not being diluted by formation water and having a wide range of sources, but they are prone to oxidation failure under high temperature and high salt, poor plugging effect of particle stacking, insufficient viscoelasticity, and difficulty in injection due to low density, which are urgent problems to be overcome.
[0003] CN114426712A discloses a rubber composition and vulcanized rubber based on nitrile rubber and styrene-butadiene rubber, the rubber composition comprising a rubber matrix, polyvinyl chloride, carbon black, white carbon black, acrylic metal salt, calcium sulfate whisker, silane coupling agent, vulcanizing agent, vulcanization accelerator, vulcanization activator, antioxidant and plasticizer. The vulcanized rubber prepared by the composition has good processing properties, low product shrinkage, good tensile strength, tear strength and anti-skid property of the vulcanized rubber, and excellent acid and alkali resistance and oil resistance. The invention does not involve research in the field of water control and oil increase in high-temperature and high-salt oil reservoirs.
[0004] CN106554513A discloses a nano-composite rubber composition and a vulcanized rubber. The nano-composite material contains nano-calcium carbonate modified by a modifier. The modifier is a substance containing a group A, a group B and a group C, wherein the group A is -S-, the group B is -COOH, and the group C is -NH 2The nanocomposite material has good dispersibility in the rubber matrix, can reinforce the rubber alone, and is beneficial to the vulcanization performance, mechanical properties and processing of the prepared rubber products, and is energy-saving and environmentally friendly. However, the performance of the nanocomposite rubber material has not been studied under high temperature and high salt conditions.
[0005] CN108300436B discloses a fracture-cavity oil reservoir oil-water selective self-expanding rubber plugging agent, which is composed of the following raw materials in parts by weight: 100 parts of nitrile rubber, 50-110 parts of water-absorbing resin, 5-15 parts of oil-swelling resin, 15-30 parts of reinforcing agent, 0.5-2 parts of softening agent, 2-5 parts of accelerator, 3-6 parts of zinc oxide and 0.5-3.5 parts of vulcanizing agent, wherein the water-absorbing resin is sodium polystyrene sulfonate, sodium polyethylene sulfonate or sodium polyallyl sulfonate. One or a mixture thereof, the oil swelling resin is one or a mixture of hydrogenated petroleum resin, phenolic resin, styrene-butadiene rubber or polyethylene resin, the vulcanized rubber is benzoyl peroxide, dicumyl peroxide or a mixture thereof, the reinforcing agent is carbon black 550, white carbon black or a mixture thereof, the softener is stearic acid, and the accelerator is zinc oxide; the plugging agent has the performance characteristics of high mechanical strength, strong resistance to mineralization, high toughness, high volume expansion ratio, etc., and the plugging mechanism is particle expansion plugging. The application scope of this patent is burial depth of 5400-6600m, temperature of 120-140℃, mineralization ≤20×10 4 mg / L of oil reservoir.
[0006] Therefore, there is an urgent need to develop modified graphite-coated soft particles that are resistant to thermal oxidation, suspended in formation water, slowly agglomerated at high temperatures, and have high plugging strength to meet the requirements of water control and oil production increase in high-temperature and high-salinity reservoirs. Summary of the invention
[0007] The purpose of the present invention is to overcome the defects of the prior art that the existing high-temperature and high-salt (≥140°C, mineralization ≥200,000 mg / L) oil reservoir rubber particle control agent is easily oxidized and fails in high-temperature and high-salt formations, is not conducive to deep injection due to low-density floating and too fast cohesion, and has no cohesion ability resulting in poor deep plugging ability. A modified graphite coated soft particle and a preparation method thereof, a profile control and water plugging agent and an application thereof are provided. The profile control and water plugging agent can, after entering the deep formation and aging for a period of time, cohere with each other, can effectively block the water channeling channel, and can effectively expand the impact.
[0008] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a modified graphite coated soft particle, wherein the modified graphite coated soft particle comprises a soft particle and a first modified graphite coated on the surface of the soft particle, wherein the soft particle comprises one or more of a rubber main agent, an antioxidant, an auxiliary antioxidant, a density regulator and a second modified graphite, and the first modified graphite and the second modified graphite are the same or different, and each is a modified graphite rich in hydroxyl groups and carboxyl groups on the surface.
[0009] The second aspect of the present invention provides a method for preparing the aforementioned modified graphite coated soft particles, wherein the preparation method comprises:
[0010] (1) contacting a rubber main agent, an antioxidant, an auxiliary antioxidant, a second modified graphite and a density regulator to perform melt kneading to obtain an integral rubber;
[0011] (2) crushing, shearing and extruding the whole rubber to obtain soft particles;
[0012] (3) Mixing a first modified graphite and water to obtain a first modified graphite dispersion, bringing the first modified graphite dispersion into contact with the soft particles, and allowing the first modified graphite to adhere to the surface of the soft particles under heating and rotating conditions to obtain modified graphite-coated soft particles.
[0013] A third aspect of the present invention provides a profile control and water plugging agent, wherein the profile control and water plugging agent is the modified graphite coated soft particles described above.
[0014] A fourth aspect of the present invention provides a use of the above-mentioned profile control and water plugging agent in an oil reservoir.
[0015] Through the above technical solution, the present invention has the following beneficial effects:
[0016] (1) The profile control and water plugging agent of the present invention can resist heat oxidation without failure in a high-temperature and high-salt formation environment, and has an effective period of ≥90 days, thereby ensuring the long-term effectiveness of the profile control and water plugging operation.
[0017] (2) The profile control and water plugging agent of the present invention has higher viscoelasticity than ordinary rubber particles, and has cohesive ability and higher plugging strength.
[0018] (3) The profile control and water plugging agent of the present invention has a density similar to that of formation water, and the density can be adjusted according to the actual density of formation water. It has the ability to slow aggregation at high temperature and begins to aggregate after aging for 2 days at high temperature. The particle size is adjustable from 200 μm to 3.5 mm, and the injection performance is good to prevent reservoir damage.
[0019] (4) The profile control and water plugging agent of the present invention has good compatibility with water bodies and is simple to prepare. It can be injected with either clean water or highly mineralized oilfield reinjection water, thereby alleviating the problem of fresh water resource shortage during complex and harsh construction processes in deserts, Gobi, oceans, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a microscope photograph of the agglomeration of the heat-resistant and salt-resistant modified graphite coated soft particles prepared with EPDM rubber as the main agent under high temperature in Example 1 of the present invention;
[0021] Figure 2 This is a microscope photograph of the agglomeration of the heat-resistant and salt-resistant modified graphite coated soft particles prepared with styrene-butadiene rubber as the main agent under high temperature in Example 2 of the present invention;
[0022] Figure 3 This is a microscope photograph of the agglomeration of the temperature-resistant and salt-resistant modified graphite coated soft particles prepared with natural rubber as the main agent under high temperature in Example 3 of the present invention;
[0023] Figure 4 This is a macroscopic schematic diagram of the temperature-resistant and salt-resistant modified graphite coated soft particles prepared in Example 3 of the present invention before and after cohesion at high temperature;
[0024] Figure 5 The thermal stability comparison of the temperature-resistant and salt-resistant modified graphite coated soft particles prepared with EPDM rubber as the main agent in Example 1 and the EPDM rubber particles in Comparative Example 1;
[0025] Figure 6 The viscoelastic modulus test results of the temperature-resistant and salt-resistant modified graphite coated soft particles prepared with EPDM rubber as the main agent at 25-150°C in Example 1;
[0026] Figure 7 The following are actual pictures of the heat-resistant and salt-resistant modified graphite coated soft particles prepared with EPDM rubber as the main agent in Examples 1, 2 and 3, which were respectively cohesive in the cores with fracture sizes of 5 mm, 8 mm and 10 mm to form plugging. DETAILED DESCRIPTION
[0027] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0028] As described above, the first aspect of the present invention provides a modified graphite coated soft particle, wherein the modified graphite coated soft particle includes a soft particle and a first modified graphite coated on the surface of the soft particle, wherein the soft particle includes one or more of a rubber main agent, an antioxidant, an auxiliary antioxidant, a density regulator and a second modified graphite, and the first modified graphite and the second modified graphite are the same or different, and each is a modified graphite rich in hydroxyl groups and carboxyl groups on the surface.
[0029] The inventors of the present invention have found that: (1) using modified graphite (first modified graphite and / or second modified graphite) as a reinforcing agent can enhance the stability of rubber particles under high temperature and high salinity, which is beneficial to the continuous plugging of rubber particles; (2) at high temperature, the soft particles coated on the surface can delay the aggregation between rubber particles, preventing the rubber particles from agglomerating too quickly under high temperature and high salinity, causing reservoir damage; (3) strengthening the viscoelasticity of the particles helps to increase the plugging effect; (4) the carboxyl and hydroxyl groups in the modified graphite can increase the hydrophilicity of the rubber particles and the electrostatic repulsion between the particles, assist in regulating the density of the rubber particles, and help the rubber particles to be evenly dispersed in the formation water and injected efficiently.
[0030] According to the present invention, the thickness of the first modified graphite coating on the surface of the soft particles is 30nm-50μm, preferably 80nm-20μm.
[0031] According to the present invention, based on the total weight of the soft particles, the content of the rubber main agent is 65-85% by weight, the content of the antioxidant is 0.1-0.5% by weight, the content of the auxiliary antioxidant is 0.05-0.3% by weight, the content of the second modified graphite is 5-10% by weight, and the content of the density regulator is 4-30% by weight; preferably, based on the total weight of the soft particles, the content of the rubber main agent is 70-80% by weight, the content of the antioxidant is 0.15-0.3% by weight, and the content of the auxiliary antioxidant is 0.1-0.2 weight %, the content of the second modified graphite is 7.5-9 weight %, the content of the density regulator is 10-25 weight %, more preferably 12.8-18.6 weight %; more preferably, based on the total weight of the soft particles, the content of the rubber main agent is 74-77 weight %, the content of the antioxidant is 0.15-0.3 weight %, the content of the auxiliary antioxidant is 0.1-0.2 weight %, the content of the second modified graphite is 7.5-8.7 weight %, and the content of the density regulator is 14-17 weight %.
[0032] In the present invention, if the content of the second modified graphite (reinforcer) is too much, it will cause the defect that the soft particles cannot cohere, seriously affecting the plugging effect. If the content of the second modified graphite (reinforcer) is too low, it will cause the defect that the soft particles cohere too quickly, causing damage to the near-well reservoir.
[0033] In the present invention, it should be noted that in the soft particles, the total content of the rubber main agent, the antioxidant, the auxiliary antioxidant, the density regulator and the second modified graphite is 100%.
[0034] According to the present invention, the first modified graphite and the second modified graphite are the same or different, each of which is a modified graphite rich in hydroxyl and carboxyl groups on the surface, and the modified graphite contains oxygen-containing groups, including hydroxyl, carboxyl and epoxy groups, and based on the total number of oxygen-containing groups in the modified graphite, the proportion of hydroxyl groups in the modified graphite is 30-60%, the proportion of carboxyl groups in the modified graphite is 10-30%, and the proportion of epoxy groups is 30-40%; preferably, based on the total number of oxygen-containing groups in the modified graphite, the proportion of hydroxyl groups in the modified graphite is 45-55%, the proportion of carboxyl groups in the modified graphite is 20-30%, and the proportion of epoxy groups in the modified graphite is 20-30%. In the present invention, the total proportion of the number of hydroxyl, carboxyl and epoxy groups is 100%.
[0035] In the present invention, the structure of the modified graphite can be as shown in the schematic diagram of formula (1), but it should be noted that the hydroxyl group and carboxyl group represented in formula (1) are not limited to the number shown in formula (1);
[0036]
[0037] According to the present invention, the particle size of the modified graphite is 200-1000 nm, preferably 300-800 nm, more preferably, the particle size of the modified graphite is 300-500 nm, and / or, the particle size of the modified graphite is 500-800 nm.
[0038] In the present invention, according to a particularly preferred embodiment, the modified graphite is natural graphite produced in a laboratory by the Hummers oxidation method, specifically:
[0039] (1) Low temperature reaction stage:
[0040] Assemble a 250mL three-necked flask in an ice water bath, add an appropriate amount of concentrated sulfuric acid, add a solid mixture of 1-5g (preferably 2g) natural nanographite powder and 1-3g (preferably 1g) sodium nitrate under stirring, then add 5-10g (preferably 6g) potassium permanganate in portions, control the reaction temperature to be lower than -5-5°C (preferably 3°C), and stir the reaction for 30-60min (preferably 45min);
[0041] (2) Medium temperature reaction stage:
[0042] Raise the temperature to about 25-50°C (preferably 35°C), and continue stirring for 30-60 minutes (preferably 45 minutes);
[0043] (3) High temperature reaction stage:
[0044] Then, a certain amount of deionized water is dripped into the mixture, and the mixture is stirred for 15-30 minutes (preferably 20 minutes). Then, a hydrogen peroxide reducing agent is added to reduce the residual oxidant in the solution, so that the solution appears bright yellow. The dispersion is then centrifuged and filtered. The washed solution is placed in an oven at 30-50° C. (preferably 35° C.) and dried, and then ground and dispersed to obtain modified graphite particles.
[0045] In the embodiments of the present invention, the modified graphite particles used are modified graphite particles prepared using the above preferred conditions.
[0046] According to the present invention, the first modified graphite (reinforcer) can form a coating on the surface of rubber particles, which delays the aggregation of rubber particles and strengthens the viscoelasticity of the particles. Secondly, it can also assist in density regulation, and its surface hydrophilic groups increase the hydrophilicity of the particles and the electrical repulsion between the particles. After reaching the deep formation, it can effectively aggregate and effectively block the crossflow channel.
[0047] According to the present invention, the rubber main agent is selected from one or more of natural rubber, styrene-butadiene rubber and EPDM rubber. The rubber main agent has excellent viscoelasticity and is the core of blocking water channeling.
[0048] According to the present invention, the antioxidant is selected from bis(2,6-di-tert-butyl-p-cresol) pentaerythritol ester and / or tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, and the antioxidant can provide a hydrogen atom to a free radical and convert itself into a relatively stable free radical. This process can interrupt the free radical chain reaction and prevent the rubber molecules from being further oxidized and damaged. Since the hindered phenol free radical is relatively stable, it is not easy to induce a new oxidation reaction, thereby effectively preventing the oxidation process.
[0049] According to the present invention, the auxiliary antioxidant is tris(2,4-di-tert-butylphenyl) phosphite, and the auxiliary antioxidant is used in conjunction with the antioxidant to improve the long-term thermal stability of the rubber material.
[0050] According to the present invention, the antioxidant and the auxiliary antioxidant can effectively prevent the particles from being oxidized and ineffective under the action of high temperature and oxygen.
[0051] According to the present invention, the density regulator is ceramic sand and / or steel shot; the ceramic sand is spherical and has a density of 3-4 g / cm 3 , preferably 3.85 g / cm 3 Preferably, the particle size of the ceramic sand is 45-90 μm; the steel shot is spherical and has a density of 7-7.5 g / cm 3 , preferably 7.2 g / cm 3 Preferably, the particle size of the steel shot is 45-75 μm. The density regulator can adjust the density of the rubber particles according to the mineralization of the formation water to make it close to the density of the formation water to achieve the purpose of suspension in the formation water, which is conducive to continuous deep injection under different formation water mineralization conditions. That is, the density regulator can adjust the density of the rubber particles, ensure that the soft particles are suspended in the water body, and help the water body carry them into the formation.
[0052] According to the present invention, the particle size of the modified graphite coated soft particles is 200 μm to 3.5 mm; preferably, the particle size of the modified graphite coated soft particles is 500 μm-2 mm.
[0053] The second aspect of the present invention provides a method for preparing the modified graphite coated soft particles, wherein the preparation method comprises:
[0054] (1) contacting a rubber main agent, an antioxidant, an auxiliary antioxidant, a second modified graphite and a density regulator to perform melt kneading to obtain an integral rubber;
[0055] (2) crushing, shearing and extruding the whole rubber to obtain soft particles;
[0056] (3) Mixing a first modified graphite and water to obtain a first modified graphite dispersion, bringing the first modified graphite dispersion into contact with the soft particles, and allowing the first modified graphite to adhere to the surface of the soft particles under heating and rotating conditions to obtain modified graphite-coated soft particles.
[0057] According to the present invention, in step (1), a twin-screw extruder contacts and melt-mixes the rubber main agent, antioxidant, auxiliary antioxidant, reinforcing agent and density regulator at 250°C; specifically, the melt-mixing conditions include: a temperature of 180-350°C, preferably 200-250°C.
[0058] According to the present invention, preferably, step (1) can be repeated 2-3 times to ensure that the antioxidant, auxiliary antioxidant, reinforcing agent and density regulator can be evenly dispersed in the rubber main agent.
[0059] According to the present invention, in step (2), the heat-resistant and salt-resistant modified graphite coated soft body is placed in a low-temperature crushing granulator to obtain heat-resistant and salt-resistant modified graphite coated soft body particles, and the obtained soft body particles are adjustable from 200μm to 3.5mm.
[0060] According to the present invention, a twin-screw extruder known to those skilled in the art may be used, wherein the conditions for extrusion granulation include: a temperature of 180-350°C, preferably 200-220°C.
[0061] According to the present invention, in step (3), the concentration of the first modified graphite dispersion is 0.1-1%.
[0062] According to the present invention, in step (3), the weight ratio of the first modified graphite dispersion to the soft particles is 100:(2-20), preferably 100:(10-15).
[0063] According to the present invention, in step (3), the conditions for heating and rotating include: a temperature of 180-200° C. and a rotation rate of 50-150 rpm.
[0064] A third aspect of the present invention provides a profile control and water plugging agent, wherein the profile control and water plugging agent is the modified graphite coated soft particles described above.
[0065] According to the present invention, the density of the profile control and water plugging agent is similar to that of the simulated formation water. Preferably, the density of the profile control and water plugging agent is 1.0-1.2 g / cm 3 .
[0066] According to the present invention, the profile control and water plugging agent disperses well in formation water, can be injected into deep areas under high temperature and then aggregated, has good viscoelasticity, and has strong long-term stability under high temperature and high salt.
[0067] According to the present invention, the profile control and water plugging agent has a first modified graphite structure with soft particles as the core and coated on the outside of the core; preferably, the soft particles contain one or more of a rubber main agent, an antioxidant, an auxiliary antioxidant, a density regulator and a second modified graphite.
[0068] According to the present invention, the profile control and water plugging agent is modified graphite coated soft particles.
[0069] According to the present invention, the particle size of the profile control and water plugging agent is 200 μm to 3.5 mm; preferably, the particle size of the profile control and water plugging agent is 500 μm-2 mm.
[0070] According to the present invention, the profile control and water plugging agent is 140°C and has a mineralization of 20×10 4 The elastic modulus under mg / L conditions is 700-800 kPa, and the viscous modulus is 350-450 kPa.
[0071] A fourth aspect of the present invention provides a use of the above-mentioned profile control and water plugging agent in an oil reservoir.
[0072] According to the present invention, the application includes: in the oil reservoir, particles of the profile control and water plugging agent are agglomerated with each other to perform plugging.
[0073] According to the present invention, the conditions of the oil reservoir include: a depth of ≥4500m, a temperature of ≥140°C, a mineralization of ≥20×10 4 mg / L; preferably, the reservoir conditions include: a depth of 4500-6500m, a temperature of 140-200°C, a mineralization of 20×10 4 mg / L to 30×10 4 mg / L.
[0074] The present invention will be described in detail below through examples.
[0075] In the following examples and comparative examples:
[0076] The microscopic cohesion map of soft particles was measured using a microscope;
[0077] Thermal stability was measured by differential scanning calorimetry;
[0078] The viscoelastic modulus parameters were measured by the rheometer high-temperature viscoelastic test method;
[0079] The core plugging rate parameter is measured by the fracture core displacement experimental method under high temperature and high salt;
[0080] The rheometer was purchased from Haake, model Haake Rheostree RS75;
[0081] The microscope was purchased from Leica Microsystems GmbH, model Leica DMi8 C;
[0082] Ceramic sand and steel shot are commercially available products from Lianzhiyan Surface Treatment Materials Co., Ltd.
[0083] EPDM rubber, styrene-butadiene rubber, and natural rubber are commercial products of Hengshui Mingguan Rubber & Plastic Products Co., Ltd.;
[0084] Antioxidants and auxiliary antioxidants are commercially available products from Shanghai Yuanye Biotechnology Co., Ltd.
[0085] Example 1
[0086] The present invention aims to explain the preparation of the temperature-resistant and salt-resistant modified graphite coated soft particles (ie, profile control and water plugging agent) of the present invention.
[0087] The soft particles include: a rubber main agent, ethylene propylene diene monomer rubber, with a mass fraction of 75%; an antioxidant, bis(2,6-di-tert-butyl-p-cresol) pentaerythritol ester, with a mass fraction of 0.3%; an auxiliary antioxidant, tris(2,4-di-tert-butylbenzene) phosphite, with a mass fraction of 0.2%; a reinforcing agent, modified graphite (second modified graphite), 300-500nm, with a mass fraction of 7.5%; a density regulator, ceramic sand, 45μm, with a mass fraction of 17%; the sum of the mass fractions of each component is 100%.
[0088] Modified graphite (first modified graphite), 300-500nm, the weight ratio of the dispersion of the first modified graphite to the soft particles is 100:10.
[0089] In addition, the structure of the modified graphite can be as shown in the schematic diagram of formula (1) in the specification. Specifically, based on the total number of oxygen-containing groups in the modified graphite, the number of hydroxyl groups in the modified graphite is 48%, the number of carboxyl groups is 28%, and the number of epoxy groups is 24%.
[0090] (1) Under the condition of 250° C. in a twin-screw extruder, 75 g of rubber particles, 0.3 g of antioxidant, 0.2 g of auxiliary antioxidant, 7.5 g of reinforcing agent (second modified graphite), and 17 g of density regulator were placed in a twin-screw extruder for melt mixing, and the mixture was repeated 3 times to ensure uniform mixing, thereby obtaining 100 g of overall rubber;
[0091] (2) Then the whole rubber is put into a low-temperature crushing granulator for fixed-size low-temperature shearing to obtain temperature-resistant and salt-resistant soft particles of a certain particle size;
[0092] (3) 100 g of a 0.1% modified graphite (first modified graphite) dispersion and 10 g of soft particles are loaded into a drum, and the modified graphite is allowed to adhere to the surface of the soft particles under heating and rotation (180°C, 100 rpm) to obtain modified graphite coated soft particles, wherein the particle size of the modified graphite coated soft particles is 0.3-0.5 mm, and the modified graphite coated soft particles include soft particles and a first modified graphite coated on the surface of the soft particles, wherein the thickness of the first modified graphite coating on the surface of the soft particles is 120 nm.
[0093] The modified graphite coated soft particles were placed in a 130℃ oven for aging as a profile control and water plugging agent. It was found that the profile control and water plugging agent particles did not settle or suspend in 200,000mg / L simulated formation water, and began to aggregate significantly after 48h. At 140℃ and a mineralization of 20×10 4 The elastic modulus is 790.30 kPa and the viscous modulus is 434.04 kPa under the condition of mg / L. After aging for 90 days, the cohesive body showed no damage.
[0094] Figure 6 This is the test result of viscoelastic modulus of heat-resistant and salt-resistant modified graphite coated soft particles prepared with EPDM rubber as the main agent and pure EPDM rubber matrix at 25-150°C. The left figure represents the elastic modulus, and the right figure represents the viscous modulus. The rubber particles after mixing are still mainly elastic, with the elasticity increased by 2.6 times and the viscosity increased by 2.5 times than that of the pure rubber matrix, which reflects the good viscoelasticity of the heat-resistant and salt-resistant modified graphite coated soft particles at high temperature, which helps to improve the sealing effect.
[0095] Example 2
[0096] The present invention aims to explain the preparation of the temperature-resistant and salt-resistant modified graphite coated soft particles (ie, profile control and water plugging agent) of the present invention.
[0097] The soft particles include: a rubber main agent, styrene-butadiene rubber, with a mass fraction of 74%; an antioxidant, bis(2,6-di-tert-butyl-p-cresol) pentaerythritol ester, with a mass fraction of 0.2%; an auxiliary antioxidant, tris(2,4-di-tert-butylbenzene) phosphite, with a mass fraction of 0.1%; a reinforcing agent, modified graphite (second modified graphite), 500-800nm, with a mass fraction of 8.7%; a density regulator, ceramic sand, 60μm, with a mass fraction of 17%; the sum of the mass fractions of each component is 100%.
[0098] Modified graphite (first modified graphite), 500-800nm, the weight ratio of the dispersion of the first modified graphite to the soft particles is 100:10.
[0099] In addition, the structure of the modified graphite can be as shown in the schematic diagram of formula (1) in the specification. Specifically, based on the total number of oxygen-containing groups in the modified graphite, the number of hydroxyl groups in the modified graphite is 51%, the number of carboxyl groups is 25%, and the number of epoxy groups is 24%.
[0100] (1) Under the condition of 250° C. in a twin-screw extruder, 74 g of rubber particles, 0.2 g of antioxidant, 0.1 g of auxiliary antioxidant, 8.7 g of reinforcing agent (second modified graphite), and 17 g of density regulator were placed in contact with each other and put into a twin-screw extruder for melt mixing, and the mixture was repeated 3 times to ensure uniform mixing, thereby obtaining 100 g of a whole rubber having the same density as simulated formation water having a mineralization degree of 200,000 mg / L (including 73282 mg / L of sodium ions, 6000 mg / L of calcium ions, and 1000 mg / L of magnesium ions);
[0101] (2) Then the whole rubber is put into a low-temperature crushing granulator for fixed-size low-temperature shearing to obtain temperature-resistant and salt-resistant soft particles of a certain particle size;
[0102] (3) 100 g of a 0.1% modified graphite (first modified graphite) dispersion and 10 g of soft particles are loaded into a drum, and the modified graphite is allowed to adhere to the surface of the soft particles under heating and rotation (200°C, 150 rpm) to obtain modified graphite coated soft particles, wherein the particle size of the modified graphite coated soft particles is 0.5-1.0 mm, and the modified graphite coated soft particles include soft particles and a first modified graphite coated on the surface of the soft particles, wherein the thickness of the first modified graphite coating on the surface of the soft particles is 1 μm.
[0103] The modified graphite coated soft particles were used as profile control and water plugging agents and aged in an oven at 130°C. It was found that the particles did not settle or suspend in 200,000 mg / L simulated formation water, and began to aggregate significantly after 48 hours. At 140°C and a mineralization of 20×10 4 The elastic modulus is 730.81 kPa and the viscous modulus is 401.34 kPa under the condition of mg / L. After aging for 90 days, the cohesive body showed no damage.
[0104] Example 3
[0105] The present invention aims to explain the preparation of the temperature-resistant and salt-resistant modified graphite coated soft particles (ie, profile control and water plugging agent) of the present invention.
[0106] The soft particles include: a rubber main agent, natural rubber, with a mass fraction of 77%; an antioxidant, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, with a mass fraction of 0.15%; an auxiliary antioxidant, tris(2,4-di-tert-butylphenyl) phosphite, with a mass fraction of 0.15%; a reinforcing agent, modified graphite (second modified graphite), 500-800nm, with a mass fraction of 8.7%; a density regulator, steel shot, 90μm, with a mass fraction of 14%; the sum of the mass fractions of each component is 100%.
[0107] Modified graphite (first modified graphite), 500-800nm, the weight ratio of the first modified graphite to the soft particles is 100:10.
[0108] In addition, the structure of the modified graphite can be as shown in the schematic diagram of formula (1) in the specification. Specifically, based on the total number of oxygen-containing groups in the modified graphite, the number of hydroxyl groups in the modified graphite is 52%, the number of carboxyl groups is 24%, and the number of epoxy groups is 24%.
[0109] (1) Under the condition of 250° C. in a twin-screw extruder, 77 g of rubber particles, 0.15 g of antioxidant, 0.15 g of auxiliary antioxidant, 8.7 g of reinforcing agent (second modified graphite), and 14 g of density regulator were placed in contact with each other and put into a twin-screw extruder for melt mixing, and the mixture was repeated 3 times to ensure uniform mixing, thereby obtaining 100 g of a whole rubber having the same density as simulated formation water having a mineralization degree of 200,000 mg / L (including 73282 mg / L of sodium ions, 6000 mg / L of calcium ions, and 1000 mg / L of magnesium ions);
[0110] (2) Then the whole rubber is put into a low-temperature crushing granulator for fixed-size low-temperature shearing to obtain temperature-resistant and salt-resistant soft particles of a certain particle size;
[0111] (3) 100 g of a 0.1% modified graphite (first modified graphite) dispersion and 100 g of soft particles are loaded into a drum, and the modified graphite is allowed to adhere to the surface of the soft particles under heating and rotation (200°C, 150 rpm) to obtain modified graphite coated soft particles, wherein the particle size of the modified graphite coated soft particles is 1.0-1.6 mm, and the modified graphite coated soft particles include soft particles and a first modified graphite coated on the surface of the soft particles, wherein the thickness of the first modified graphite coating on the surface of the soft particles is 500 nm.
[0112] The modified graphite coated soft particles were used as profile control and water plugging agents and aged in an oven at 130°C. It was found that the particles did not settle or suspend in 200,000 mg / L simulated formation water, and began to aggregate significantly after 48 hours. At 140°C and a mineralization of 20×10 4 The elastic modulus is 692.38 kPa and the viscous modulus is 387.22 kPa under the condition of mg / L. After aging for 90 days, the cohesive body showed no damage.
[0113] Figure 1 This is a microscope photo of the heat-resistant and salt-resistant modified graphite coated soft particles prepared with EPDM rubber as the main agent before and after aggregation at high temperature in Example 1 of the present invention; Figure 2 This is a microscope photograph of the agglomeration of the temperature-resistant and salt-resistant modified graphite coated soft particles prepared with styrene-butadiene rubber as the main agent under high temperature prepared in Example 2 of the present invention; Figure 3 is a microscope photograph of the high-temperature agglomeration of the temperature-resistant and salt-resistant modified graphite coated soft particles prepared with natural rubber as the main agent in Example 1 of the present invention, wherein it should be noted that Figure 1-3 The left pictures show that the interface of the coated soft particles is clear before the aggregation, and the right pictures show that after the aggregation, the interfaces are obviously aggregated. Figure 1 , 2 3 It can be seen that after the rubber particles are aged at high temperature for 2 days, the interface between the particles begins to cohere, and the single small particles are transformed into large-sized aggregated particles, which can block larger-scale cracks.
[0114] Figure 4 It is a macroscopic schematic diagram of the heat-resistant and salt-resistant modified graphite coated soft particles prepared in Example 3 of the present invention before and after aggregation at high temperature. The figure on the left shows that the coated soft particles are dispersed in water, and the figure on the right shows that the particles aggregate at high temperature to form an effective blockage for the water body. It can be seen from the figures that the rubber particles after aggregation can indeed effectively block the water body.
[0115] Figure 7 The heat-resistant and salt-resistant modified graphite coated soft particles prepared in Examples 1, 2, and 3 are respectively coagulated in the cores with fracture sizes of 5 mm, 8 mm, and 10 mm to form plugging. Figure 7 It can be seen that the temperature-resistant and salt-resistant modified graphite coated soft particles form effective plugging in cracks of different sizes.
[0116] Example 4
[0117] The present invention aims to explain the preparation of the temperature-resistant and salt-resistant modified graphite coated soft particles (ie, profile control and water plugging agent) of the present invention.
[0118] The temperature-resistant and salt-resistant modified graphite coated soft particles were prepared in the same manner as in Example 1, except that:
[0119] The soft particles include: a rubber main agent, ethylene propylene diene monomer rubber, with a mass fraction of 62.2 weight percent; an antioxidant, bis(2,6-di-tert-butyl-p-cresol) pentaerythritol ester, with a mass fraction of 0.5 weight percent; an auxiliary antioxidant, tris(2,4-di-tert-butylbenzene) phosphite, with a mass fraction of 0.3 weight percent; a reinforcing agent (second modified graphite), modified graphite, 500-1000 nm, with a mass fraction of 10 weight percent; a density regulator, ceramic sand, 45 μm, with a mass fraction of 27 weight percent; the sum of the mass fractions of each component is 100%.
[0120] Modified graphite (first modified graphite), 500-1000 nm, the weight ratio of the dispersion of the first modified graphite to the soft particles is 100:10.
[0121] In addition, the structure of the modified graphite can be as shown in the schematic diagram of formula (1) in the specification. Specifically, based on the total number of oxygen-containing groups in the modified graphite, the number of hydroxyl groups, carboxyl groups and epoxy groups in the modified graphite is 57%, 11% and 32%.
[0122] As a result, modified graphite coated soft particles were prepared, wherein the particle size of the modified graphite coated soft particles was 0.3-0.5 mm, and the modified graphite coated soft particles included soft particles and a first modified graphite coated on the surface of the soft particles, wherein the thickness of the first modified graphite coated on the surface of the soft particles was 50 nm.
[0123] Example 5
[0124] The present invention aims to explain the preparation of the temperature-resistant and salt-resistant modified graphite coated soft particles (ie, profile control and water plugging agent) of the present invention.
[0125] The temperature-resistant and salt-resistant modified graphite coated soft particles were prepared in the same manner as in Example 1, except that:
[0126] The soft particles include: a rubber main agent, ethylene propylene diene monomer rubber, with a mass fraction of 82%; an antioxidant, bis(2,6-di-tert-butyl-p-cresol) pentaerythritol ester, with a mass fraction of 0.3%; an auxiliary antioxidant, tris(2,4-di-tert-butylbenzene) phosphite, with a mass fraction of 0.1%; a reinforcing agent, modified graphite (second modified graphite), 300-500nm, with a mass fraction of 5%; a density regulator, ceramic sand, 45μm, with a mass fraction of 12.6%; the sum of the mass fractions of each component is 100%.
[0127] Modified graphite (first modified graphite), 300-500nm, the weight ratio of the dispersion of the first modified graphite to the soft particles is 100:10.
[0128] In addition, the structure of the modified graphite can be as shown in the schematic diagram of formula (1) in the specification. Specifically, based on the total number of oxygen-containing groups in the modified graphite, the number of hydroxyl groups, carboxyl groups and epoxy groups in the modified graphite is 55%, 12% and 33%.
[0129] As a result, modified graphite coated soft particles were prepared, wherein the particle size of the modified graphite coated soft particles was 0.3-0.5 mm, and the modified graphite coated soft particles included soft particles and a first modified graphite coated on the surface of the soft particles, wherein the thickness of the first modified graphite coated on the surface of the soft particles was 30 μm.
[0130] Application Example 1
[0131] The present invention also provides an application method of the heat-resistant and salt-resistant modified graphite coated soft particles as a profile control and water plugging agent; the heat-resistant and salt-resistant modified graphite coated soft particles of 0.3-0.5 mm prepared in Example 1 are selected for fracture plugging experiments, the salinity of the simulated formation water is 200,000 mg / L (including 73282 mg / L of sodium ions, 6000 mg / L of calcium ions, and 1000 mg / L of magnesium ions), the core fracture size is 5 mm, the injection volume is 1 FV, the injection aging temperature is 150 ° C, the aging time is 48 h, and the permeability before plugging is 2.69×10 6 mD, and the permeability after injection is 31.58mD.
[0132] Application Example 2
[0133] The present invention also provides an application method of heat-resistant and salt-resistant modified graphite coated soft particles as a profile control and water plugging agent; the heat-resistant and salt-resistant modified graphite coated soft particles of 0.5-1.0 mm prepared in Example 2 are selected for fracture plugging experiments, the salinity of the simulated formation water is 200,000 mg / L (including 73282 mg / L of sodium ions, 6000 mg / L of calcium ions, and 1000 mg / L of magnesium ions), the core fracture size is 8 mm, the injection volume is 1 FV, the injection aging temperature is 150 ° C, the aging time is 48 h, and the permeability before plugging is 17.33×10 6 mD, and the permeability after injection is 109.20mD.
[0134] Application Example 3
[0135] The present invention also provides an application method of heat-resistant and salt-resistant modified graphite coated soft particles as a profile control and water plugging agent; the heat-resistant and salt-resistant modified graphite coated soft particles of 1.0-1.6 mm prepared in Example 3 are selected for fracture plugging experiments, the salinity of the simulated formation water is 200,000 mg / L (including 73282 mg / L of sodium ions, 6000 mg / L of calcium ions, and 1000 mg / L of magnesium ions), the core fracture size is 10 mm, the injection volume is 1 FV, the injection aging temperature is 150 ° C, the aging time is 48 h, and the permeability before plugging is 42.35×10 6 mD, and the permeability after injection is 279.47mD.
[0136] Application Example 4
[0137] The present invention also provides an application method of heat-resistant and salt-resistant modified graphite coated soft particles as a profile control and water plugging agent; the heat-resistant and salt-resistant modified graphite coated soft particles of 1.0-1.6 mm prepared in Example 3 are selected for fracture plugging experiments, the salinity of the simulated formation water is 200,000 mg / L (including 73282 mg / L of sodium ions, 6000 mg / L of calcium ions, and 1000 mg / L of magnesium ions), the core fracture size is 15 mm, the injection volume is 1 FV, the injection aging temperature is 150 ° C, the aging time is 48 h, and the permeability before plugging is 214.61×10 6 mD, and the permeability after injection is 319.55mD.
[0138] Application Example 5
[0139] The present invention also provides an application method of heat-resistant and salt-resistant modified graphite coated soft particles as a profile control and water plugging agent; the 0.3-0.5 mm heat-resistant and salt-resistant modified graphite coated soft particles prepared in Example 4 are selected for fracture plugging experiments, the salinity of the simulated formation water is 200,000 mg / L (including 73282 mg / L of sodium ions, 6000 mg / L of calcium ions, and 1000 mg / L of magnesium ions), the core fracture size is 5 mm, the injection volume is 1 FV, the injection aging temperature is 150 ° C, the aging time is 48 h, and the permeability before plugging is 2.71×10 6 mD, and the permeability after injection is 48.77mD.
[0140] Application Example 6
[0141] The present invention also provides an application method of heat-resistant and salt-resistant modified graphite coated soft particles as a profile control and water plugging agent; the 0.3-0.5 mm heat-resistant and salt-resistant modified graphite coated soft particles prepared in Example 5 are selected for fracture plugging experiments, the salinity of the simulated formation water is 200,000 mg / L (including 73282 mg / L of sodium ions, 6000 mg / L of calcium ions, and 1000 mg / L of magnesium ions), the core fracture size is 5 mm, the injection volume is 1 FV, the injection aging temperature is 150 ° C, the aging time is 48 h, and the permeability before plugging is 2.70×10 6 mD, and the permeability after injection is 62.51mD.
[0142] Comparative Example 1
[0143] The EPDM rubber matrix in Example 1, that is, only EPDM rubber, and no antioxidant, auxiliary antioxidant, first modified graphite, second modified graphite, and density regulator, was selected. Aging was performed at the same temperature and mineralization, and the rubber particles rapidly aggregated after 0.5 h, and after aging for 20 days, the rubber particles aggregated significantly oxidized and discolored, and the volume began to collapse.
[0144] Figure 5It is a comparison of the thermal stability of the heat-resistant and salt-resistant modified graphite coated soft particles prepared with EPDM rubber as the main agent in Example 1 (right picture) and the EPDM rubber particles in Comparative Example 1 (left picture). The heat-resistant and salt-resistant modified graphite coated soft particles that are slowly polymerized under formation water of equal density and high temperature do not show other impurity peaks. Comparative Example 1 (the picture on the left) shows the thermal stability of the rubber matrix, and Example 1 (the picture on the right) shows the thermal stability of the coated soft particles, indicating that the mixing effect is better, and the density regulator and graphite will not affect the excellent temperature resistance of the rubber particles themselves, and may even improve it to a certain extent.
[0145] Comparative Example 2
[0146] The styrene-butadiene rubber matrix in Example 2, that is, only styrene-butadiene rubber, and no antioxidant, auxiliary antioxidant, first modified graphite, second modified graphite, and density modifier, was selected. Aging was performed at the same temperature and salinity, and the rubber particles rapidly aggregated after 0.5 h, and after aging for 35 days, the rubber particles aggregated significantly oxidized and discolored, and the volume began to collapse.
[0147] Comparative Example 3
[0148] The natural rubber matrix in Example 3, that is, only natural rubber, not including antioxidant, auxiliary antioxidant, first modified graphite, second modified graphite and density regulator, was selected. Aging was carried out at the same temperature and mineralization, and rapid cohesion occurred in 0.5h, and after aging for 60 days, the rubber particle cohesion was obviously oxidized and discolored, and the volume began to collapse.
[0149] Comparative Example 4
[0150] The rubber particles were prepared in the same manner as in Example 1, except that the components were different, and the EPDM rubber matrix in Example 1 was selected, that is, including EPDM rubber, antioxidant, auxiliary antioxidant, second modified graphite, and density regulator, but not including first modified graphite. The rubber particles were aged at the same temperature and mineralization, and rapidly aggregated in 0.5 h, but no obvious oxidation occurred in the aggregates of the rubber particles after aging for 60 days.
[0151] Comparative Example 5
[0152] The rubber particles were prepared in the same manner as in Example 2, except that the content of the components was different, and the styrene-butadiene rubber matrix in Example 2 was selected, that is, including styrene-butadiene rubber, antioxidant, auxiliary antioxidant, first modified graphite, second modified graphite and density regulator, except that the content of the first modified graphite was increased to twice the original amount. When aged at the same temperature and mineralization, the cohesion effect was significantly weakened, and no significant oxidation occurred in the rubber particle cohesion after aging for 60 days.
[0153] Comparative Example 6
[0154] The rubber particles were prepared in the same manner as in Example 3, except that the content of the components was different, and the natural rubber matrix in Example 3 was selected, that is, only natural rubber, antioxidant, auxiliary antioxidant, first modified graphite, second modified graphite and density regulator were included. The difference was that the content of the first modified graphite was reduced to half of the original. Aging was performed at the same temperature and mineralization, and the rubber particles aggregated quickly after 10 hours, and the viscoelasticity was significantly reduced, but no obvious oxidation occurred in the rubber particle aggregates after aging for 60 days.
[0155] Comparative Example 7
[0156] The rubber particles were prepared in the same manner as in Example 1, except that the EPDM rubber matrix in Example 1 was selected, i.e., including EPDM rubber, antioxidant, auxiliary antioxidant, density regulator and reinforcing agent, but the "reinforcing agent (first modified graphite and second modified graphite) in Example 1" was replaced by "natural nanographite without hydrophilic groups on the surface". Due to insufficient hydrophilicity and surface negative charge, the obtained soft particles had poor dispersibility in water, which affected the injection effect, and the cohesion rate was shortened to 40h at high temperature.
[0157] Application Comparative Example 1
[0158] The plugging experiment was carried out in the same manner as in Example 1, except that the carbon black reinforced rubber particles, i.e., the rubber particles prepared in Comparative Example 1, had a permeability of 2.69×10 6 mD, and the permeability after injection is 2831.58mD.
[0159] Application Comparative Example 2
[0160] The plugging experiment was carried out in the same manner as in Example 2, except that the carbon black reinforced rubber particles, i.e., the rubber particles prepared in Comparative Example 2, had a permeability of 17.33×10 6 mD, and the permeability after injection is 36609.62mD.
[0161] Application Comparative Example 3
[0162] The plugging experiment was carried out in the same manner as in Application Example 3, except that the rubber particles were pure rubber particles, i.e., the rubber particles prepared in Comparative Example 3, which were not mixed with other additives, floated on the surface of the formation water and were not easy to inject. After being pre-buried and aged in the core for 2 hours, a complete plugging effect was formed, causing reservoir damage.
[0163] Application Comparative Example 4
[0164] The plugging experiment was carried out in the same way as in Application Example 4, except that the particles were pure rubber particles, without any other additives, and floated on the surface of the formation water, making it difficult to inject. After being pre-buried and aged in the core for 2 hours, a complete plugging effect was formed, making subsequent injection impossible.
[0165] Application Comparative Example 5
[0166] The soft particles prepared in Comparative Example 4 were used to conduct a plugging experiment in the same manner as in Application Example 2. However, due to the lack of a reinforcing agent, the particles agglomerated too quickly to be injected, and insufficient viscoelasticity resulting in poor resistance to formation water scouring, the plugging effect was poor.
[0167] Application Comparative Example 6
[0168] The soft particles prepared in Comparative Example 5 were used to carry out a plugging experiment in the same manner as in Application Example 2. Due to the excessive amount of reinforcing agent, the particles lost most of their cohesive ability, and the permeability before plugging was 17.33×10 6 mD, and the permeability after injection is 32658.22mD.
[0169] Application Comparative Example 7
[0170] The soft particles prepared in Comparative Example 6 were used to carry out the plugging experiment in the same manner as in Application Example 2. The particles aggregated quickly. After aging for 12 hours, the lack of reinforcing agent resulted in insufficient viscoelasticity, which in turn led to poor plugging effect. The permeability before plugging was 17.33×10 6 mD, and the permeability after injection is 21390.42mD.
[0171] Application Comparative Example 8
[0172] The soft particles prepared in Comparative Example 7 were used to carry out a plugging experiment in the same manner as in Application Example 2. Since the enhancer no longer imparts hydrophilicity and negative charge to the soft particles, the particles have poor dispersion in the formation water, which is not conducive to injection, and the aggregation rate is accelerated, which is not conducive to deep migration.
[0173] In summary, the heat-resistant and salt-resistant modified graphite coated soft particles prepared by the present invention, wherein the antioxidant provides a hydrogen atom to the free radical, and itself is converted into a relatively stable free radical. This process can interrupt the free radical chain reaction and prevent the rubber molecules from being further oxidized and damaged. Since the hindered phenol free radical is relatively stable, it is not easy to trigger a new oxidation reaction, thereby effectively preventing the oxidation process; the auxiliary antioxidant is used in conjunction with the antioxidant to improve the long-term thermal stability of the rubber material; the coating effect of the first modified graphite can delay the cohesion between the soft particles and prevent damage to the near-well reservoir. The second modified graphite enhances the viscoelasticity of the particles and strengthens the plugging effect, and also has the functions of auxiliary density adjustment and auxiliary dispersion; the density regulator can adjust the density of the rubber particles according to the mineralization of the formation water so that it is close to the density of the formation water to achieve the purpose of suspension in the formation water, which is conducive to continuous deep injection under different formation water mineralization conditions. The soft particles can cohere for 2 days under high temperature and high salt to form a large-sized and high-strength aggregate, which can control the water discharge from the fracture cave, and the stability is ≥90 days.
[0174] Compared with the embodiment, the above-mentioned comparative examples 1, 2, and 3 are not stable enough under high temperature and high salt conditions after aging. This is because the rubber particles are easily oxidized and destroyed under high temperature and high salt conditions due to the lack of antioxidants and auxiliary antioxidants. The lack of strengtheners and density regulators leads to poor viscoelasticity and dispersibility, which is not conducive to injection and plugging.
[0175] Compared with the examples, the above comparative examples 4-7 have poor viscoelasticity / dispersibility of the particles due to changes in the properties or dosage of the reinforcing agent.
[0176] The above-mentioned comparative examples 1 and 2 have a higher permeability after plugging than the embodiment. The main reason for the poor plugging effect is that the carbon black reinforced rubber particles do not have the cohesive ability and only rely on their own plugging effect, so the plugging effect of small-sized particles is poor.
[0177] Since the above-mentioned application comparative examples 3 and 4 do not have a density adjuster, the density is too low and they can only agglomerate and float on the surface of the formation water, which is not conducive to injection; in addition, the unmodified graphite on the surface of the rubber particles delays the adhesion between the particles, causing the particles to immediately adhere under the influence of temperature, resulting in blockage of the near-well area, causing reservoir damage and making it impossible to control deep source water.
[0178] In the above-mentioned comparative examples 5-8, since the strengthening agent has a different range and characteristics from those proposed in the present invention, the soft particles are lacking in cohesiveness / injectability / sealing properties, resulting in poor actual injection and sealing effects.
[0179] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A modified graphite coated soft particle, characterized in that: The modified graphite coated soft particles include soft particles and a first modified graphite coated on the surface of the soft particles, wherein the soft particles include one or more of a rubber main agent, an antioxidant, an auxiliary antioxidant, a density regulator and a second modified graphite, and the first modified graphite and the second modified graphite are the same or different, and each is a modified graphite rich in hydroxyl groups and carboxyl groups on the surface.
2. The modified graphite coated soft particles according to claim 1, wherein The thickness of the first modified graphite coating on the surface of the soft particles is 30nm-50μm, preferably 80nm-20μm.
3. The modified graphite coated soft particles according to claim 1 or 2, wherein: The modified graphite contains oxygen-containing groups, including hydroxyl groups, carboxyl groups and epoxy groups, and based on the total number of oxygen-containing groups in the modified graphite, the number of hydroxyl groups accounts for 30-60%, the number of carboxyl groups accounts for 10-30%, and the number of epoxy groups accounts for 30-40%; And / or, the particle size of the modified graphite is 200-1000 nm, preferably 300-800 nm, more preferably, the particle size of the modified graphite is 300-500 nm, and / or, the particle size of the modified graphite is 500-800 nm.
4. The modified graphite coated soft particles according to any one of claims 1 to 3, wherein: Based on the total weight of the soft particles, the content of the rubber main agent is 65-85% by weight, the content of the antioxidant is 0.1-0.5% by weight, the content of the auxiliary antioxidant is 0.05-0.3% by weight, the content of the second modified graphite is 5-10% by weight, and the content of the density regulator is 4-30% by weight; Preferably, based on the total weight of the soft particles, the content of the rubber main agent is 70-80 weight %, the content of the antioxidant is 0.15-0.3 weight %, the content of the auxiliary antioxidant is 0.1-0.2 weight %, the content of the second modified graphite is 7.5-9 weight %, and the content of the density regulator is 10-25 weight %.
5. The modified graphite coated soft particles according to any one of claims 1 to 4, wherein: The rubber main agent is selected from one or more of natural rubber, styrene-butadiene rubber and EPDM rubber; And / or, the antioxidant is selected from bis(2,6-di-tert-butyl-p-cresol)pentaerythritol ester and / or tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid]pentaerythritol ester; And / or, the auxiliary antioxidant is tris(2,4-di-tert-butylphenyl) phosphite; And / or, the density regulator is ceramic sand and / or steel shot; Preferably, the particle size of the ceramic sand is 45-90 μm; Preferably, the steel shot has a particle size of 45-75 μm.
6. The modified graphite coated soft particles according to any one of claims 1 to 5, wherein: The particle size of the modified graphite coated soft particles is 200 μm to 3.5 mm; preferably, the particle size of the modified graphite coated soft particles is 500 μm-2 mm.
7. A method for preparing the modified graphite coated soft particles according to any one of claims 1 to 6, characterized in that: The preparation method comprises: (1) contacting a rubber main agent, an antioxidant, an auxiliary antioxidant, a second modified graphite and a density regulator to perform melt kneading to obtain an integral rubber; (2) crushing, shearing and extruding the whole rubber to obtain soft particles; (3) Mixing a first modified graphite and water to obtain a first modified graphite dispersion, bringing the first modified graphite dispersion into contact with the soft particles, and allowing the first modified graphite to adhere to the surface of the soft particles under heating and rotating conditions to obtain modified graphite-coated soft particles.
8. The preparation method according to claim 7, wherein: In step (1), the melt mixing conditions include: a temperature of 180-350°C; And / or, in step (2), the conditions for extrusion granulation include: a temperature of 180-350°C; And / or, in step (3), the conditions of the heating rotation include: a temperature of 180-200° C. and a rotation rate of 50-150 rpm; and / or, in step (3), the concentration of the first modified graphite dispersion is 0.1-1%; And / or, in step (3), the weight ratio of the first modified graphite dispersion to the soft particles is 100:(5-20).
9. A profile control and water plugging agent, characterized in that: The profile control and water plugging agent is the modified graphite coated soft particles described in any one of claims 1 to 6.
10. The profile control and water plugging agent according to claim 9, wherein: The profile control and water plugging agent is 140°C and has a mineralization of 20×10 4 The elastic modulus under mg / L conditions is 700-800 kPa, and the viscous modulus is 350-450 kPa; And / or, the density of the profile control and water plugging agent is 1-1.2 g / cm 3 .
11. Use of the profile control and water plugging agent according to claim 9 or 10 in oil reservoirs.
12. The use according to claim 11, wherein: The application includes: in the oil reservoir, the particles of the profile control and water plugging agent are agglomerated to perform plugging; And / or, the conditions of the oil reservoir include: depth ≥4500m, temperature ≥140°C, mineralization ≥20×10 4 mg / L; Preferably, the conditions of the oil reservoir include: a depth of 4500-6500 m, a temperature of 140-200 ° C, a mineralization of 20×10 4 mg / L to 30×10 4 mg / L.
Citation Information
Patent Citations
Water plugging profile control agent
CN101885961A
Asphalt composition particle and preparation method thereof
CN103102705A
High-temperature-resistant and high-salt-resistant oil reservoir profile modifying water plugging agent and preparation method thereof
CN105400503A
Polymer gel composite plugging agent and preparation method thereof
CN111019617A
Temperature-resistant and salt-resistant modified nano-graphite gel dispersion system and gel dispersion with strong self-growth effect as well as preparation method and application of temperature-resistant and salt-resistant modified nano-graphite gel dispersion system and gel dispersion
CN115322759A
